2017
DOI: 10.18632/oncotarget.18439
|View full text |Cite
|
Sign up to set email alerts
|

Correction: p63α modulates c-Myc activity via direct interaction and regulation of MM1 protein stability

Abstract: Present:In the title and abstract, the 'β' symbol was mistakenly inserted instead of 'α'. The title should read p63α modulates c-Myc activity via direct interaction and regulation of MM1 protein stability All symbols of "β" in the ABSTRACT should be changed into "α". p63β modulates c-Myc activity via direct interaction and ABSTRACTBoth p53-related p63 and c-Myc are transcription factors playing key roles in cell proliferation, survival, development and tumorigenesis. In the present study, we identified that MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…In contrast to previous studies showing that c-Myc could be posttranslationally regulated (55), as well as our published study showing that c-Myc protein degradation is regulated by FBW7 in arsenite-treated cells (56), Han and colleagues report that c-Myc activity is modulated by p63␣ via direct protein-protein interaction in B-cell acute lymphoblastic leukemia (57). In our current study, we have demonstrated that p63␣ overexpression promotes c-Myc mRNA degradation, thereby inhibiting c-Myc protein expression in BC cells.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous studies showing that c-Myc could be posttranslationally regulated (55), as well as our published study showing that c-Myc protein degradation is regulated by FBW7 in arsenite-treated cells (56), Han and colleagues report that c-Myc activity is modulated by p63␣ via direct protein-protein interaction in B-cell acute lymphoblastic leukemia (57). In our current study, we have demonstrated that p63␣ overexpression promotes c-Myc mRNA degradation, thereby inhibiting c-Myc protein expression in BC cells.…”
Section: Discussioncontrasting
confidence: 99%